ANALISIS PROKSIMAT PAKAN BUATAN DENGAN PENAMBAHAN HIDROLISAT TEPUNG BULU AYAM SEBAGAI SUMBER PROTEIN ALTERNATIF BAGI IKAN NILA (Oreochromis sp.) - Dwi Tika Afriani; Uswatul Hasan (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
Feed protein sources for fish so far have fluctuated and still have to be imported from abroad, causing difficulties for farmers. Then you need to look for other sources of protein that are cheaper and easier to obtain. This study aims to determine the effect of increasing the value of protein content in artificial feed added to chicken feather flour hydrolyzate and to find out the best composition of chicken feather meal hydrolyzate added in the artificial feed that provides optimal protein levels for tilapia growth. This research method is an experiment using a completely randomized design (CRD) with three treatments and three replications. Control (-): 100% conventional artificial feed (PB). Control (+): 100% Chicken Feather Flour (TBA). Treatment A: 25% TBA and 75% PB. Treatment B: 50% TBA 50% PB. Treatment C: 75% TBA and 25% PB. Proximate tests performed on each sample. The parameters observed were crude protein levels and organoleptic tests. They are analyzed using ANAVA and DMRT tests with a confidence level of 95%, while for organoleptic yield data were analyzed descriptively qualitatively. The results showed that TBA fermentation with B. subtillis could improve the quality of raw materials for fish feed. The highest increase in crude protein in treatment C (10.40 ± 0.22) with a change in physical properties to brown, pungent odor, and blindness texture.